Pemanfaatan Sumber Daya Alam Pesisir Pantai Bali Lestari Sebagai Penunjang Pembangunan Pariwisata - Ayu Fitriana; Najwa Felisha Lubis; Khoirul Azis; Valen Zikra Febix; Sari Wulandari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the utilization of coastal natural resources of Pantai Bali Lestari in supporting sustainable tourism development in Serdang Bedagai Regency. Pantai Bali Lestari is a real example of tourism destination management based on local wisdom and cultural commodification, especially Balinese culture, to attract tourists. Various facilities and infrastructure such as photo spots, restaurants, lodging, and adaptation of Balinese architecture make this beach a leading destination. However, coastal area management also faces challenges, both from environmental, social, and economic aspects. This study uses a descriptive qualitative approach with data collection through field observations, documentation, and literature studies. The results of the study indicate that synergy between the government, tourism managers, and the surrounding community is very important in ensuring the sustainability of coastal areas as productive and environmentally friendly tourism assets.